A comparative study between coblation adenoidectomy and conventional adenoidectomy - Saravana Selvan, V.; Silambu, Muthamil; Vinodh Kumaran, D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The objective of the study was to compare the advantages and results between coblation adenoidectomy and conventional adenoidectomy by curettage. Methods: The study was conducted in Stanley medical college, Chennai (a tertiary care centre) from June 2013 to June 2016. Fifty patients were studied who underwent adenoidectomy. Twenty five patients underwent conventional adenoidectomy by curettage and rest by nasal endoscopy assisted coblation adenoidectomy. Following outcomes were evaluated: pain score on first day, days reporting pain, analgesic days, school absenteeism, endoscopic adenoid grading and intraoperative bleeding. Results: Patients who underwent coblation adenoidectomy showed better results during follow up with lesser complications. Conclusions: Coblation adenoidectomy is a better technique when compared to conventional technique of curettage.